Rice with lower amylose content could have reduced starch digestibility due to crystallized resistant starch synthesized by linearized amylopectin - Sahoo, Upasana; Biswal, Monalisha; Nayak, Lopamudra; Kumar, Ravinder; Tiwari, Rahul Kumar; Lal, Milan Kumar; Bagchi, Torit Baran; Sah, Rameswar Prasad; Singh, Nihar Ranjan; Sharma, Srigopal; Nayak, Amaresh Kumar; Kumar, Awadhesh (Journal of the science of food and agriculture, 2025)
BACKGROUND High resistant starch (RS) rice with a low glycemic index (GI) is digested more slowly, resulting in a slow increase in the postprandial blood glucose level. People with milled rice as a staple diet, and with sedentary lifestyles, are more prone to acquire type 2 diabetes in the long term. With an increasing population of diabetics worldwide, one possible solution is the development of rice‐based, low‐GI foods with high RS content rice. In addition to amylose content (AC), linear chains of amylopectin also affect the rate of starch digestibility. RESULTS The values of GI (52.49–63.0), RS (0.64% to 2.28%), and AC (3.82% to 24.52%) were found to vary widely in 110 rice genotypes. Genotypes IG 23 and IG 40, with contrasting AC (15.65% and 24.52%, respectively), revealed that amylose alone did not affect digestion rate. Starch morphology, bioaccessibility, and pasting properties differed noticeably among genotypes. A starch debranching enzyme pullulanase assay indicated the role of the linear amylopectin chain in crystallized RS formation within the grains of lower AC genotype IG 23. CONCLUSION Enhanced activity of the starch‐debranching enzyme pullulanase produced linearized amylopectin resulted into reduced starch digestibility in low‐amylose rice. This is probably the first report on the natural presence of high RS (crystallized) in rice with lower AC (IG 23). Development of rice‐based food with low GI and high RS could be a promising strategy for lowering the prevalence of type 2 diabetes. © 2024 Society of Chemical Industry.